2021
DOI: 10.1111/jre.12866
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐derived small extracellular vesicles as cell‐free therapy: Perspectives in periodontal regeneration

Abstract: Mesenchymal stem cells (MSC) are involved in the regeneration of the different missing or compromised periodontal tissues. MSC‐derived small extracellular vesicles (sEV) have recently been explored as a favorable substitution for stem cell therapy, as they are capable of producing therapeutic effects comparable to those of their parent cells, with advantages over cell therapy. The aim of this review is to evaluate the use of mesenchymal stem cells (MSC)‐derived sEV as cell‐free therapy in periodontal regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In fact, multiple researchers have found that exosomes released from MSCs from different sources can differentially alleviate periodontitis and promote periodontal regeneration. 17 Among all sources of MSCs, dental pulp stem cells (DPSCs) have attracted particular attention because relative to BMSCs, they are readily accessible, less tumorigenic and demonstrate increased osteogenic and proliferative activity, showing greater capacity for the treatment of periodontitis. 18 20 In this context, we have conducted a number of studies to expand the understanding of DPSCs and facilitate their clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, multiple researchers have found that exosomes released from MSCs from different sources can differentially alleviate periodontitis and promote periodontal regeneration. 17 Among all sources of MSCs, dental pulp stem cells (DPSCs) have attracted particular attention because relative to BMSCs, they are readily accessible, less tumorigenic and demonstrate increased osteogenic and proliferative activity, showing greater capacity for the treatment of periodontitis. 18 20 In this context, we have conducted a number of studies to expand the understanding of DPSCs and facilitate their clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the well-repair of alveolar bone loss caused by periodontal diseases or other pathological stimuli is of great significance to ensure the structural integrity and functional coordination of periodontal tissues [ 51 ]. To date, there is still an unmet need for novel cell-free regenerative therapies, which are expected to bring favorable prognoses and avoid the problems associated with the direct administration of stem cells [ 14 , 17 ]. This study demonstrated that DFC-derived CRMVs significantly strengthened alveolar bone regeneration and achieved a comparative therapeutic level of MSCs-based treatment in a murine periodontal defect model.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional therapies, including guided tissue regeneration (GTR), autologous bone grafting and heterogeneous bone filling, have obtained some successful cases, but commonly showed limited efficacy, prolonged therapeutic period and even secondary injuries in some complex conditions [ 7 9 ]. Additionally, mesenchymal stem cells (MSCs)-based therapies exhibited curative effects [ 10 ], while the associated inflammatory responses and safety issues seem inevitable [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a cell-free approach, centered around cell products (i.e., EVs derived from these cells), has been proposed, and there is an emerging focus on cell-derived EVs as potential therapeutic agents to promote periodontal regeneration. The utilization of sEVs for dental tissue regeneration is emerging as a viable cell-free treatment option, with ‘proof of concept’ studies reported using bone marrow or adipose MSC-derived sEVs (reviewed in [ 41 , 42 , 43 ]); yet, periodontal or dental pulp cell sources are likely to uniquely reflect the functional complexity of the periodontium and oral cavity.…”
Section: The Source and Characteristics Of Periodontal (Dental Pulp) Cellsmentioning
confidence: 99%